1986
DOI: 10.1152/ajpendo.1986.251.1.e127
|View full text |Cite
|
Sign up to set email alerts
|

Galanin: a novel pancreatic neuropeptide

Abstract: Immunofluorescent staining for galanin in canine pancreatic tissue was performed together with an evaluation of the effects of synthetic galanin on pancreatic output of glucagon, somatostatin, and insulin in pentobarbital-anesthetized dogs. A dense network of galaninlike immunoreactive nerve fibers was visualized in association with the islets of Langerhans and occasional galanin immunoreactive fibers were seen to course through the exocrine parenchyma of dog pancreas. During intravenous infusion of synthetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
117
0
2

Year Published

1989
1989
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(129 citation statements)
references
References 14 publications
10
117
0
2
Order By: Relevance
“…Galanin and NPY are also localised to nerve cell bodies in the celiac ganglion, as shown in dogs [56]. Furthermore, galanin is released from the pancreas upon electrical activation of the sympathetic nerves [77] and galanin and NPY both inhibit insulin secretion, in vivo and in vitro [77±81]. The involvement of galanin in inhibition of insulin secretion induced by activation of sympathetic nerves is particularly important in dogs, where galanin is released into the venous effluent of the pancreas during pancreatic sympathetic stimulation in a quantity which is sufficient to inhibit insulin secretion [82].…”
Section: Sympathetic Nervesmentioning
confidence: 99%
See 2 more Smart Citations
“…Galanin and NPY are also localised to nerve cell bodies in the celiac ganglion, as shown in dogs [56]. Furthermore, galanin is released from the pancreas upon electrical activation of the sympathetic nerves [77] and galanin and NPY both inhibit insulin secretion, in vivo and in vitro [77±81]. The involvement of galanin in inhibition of insulin secretion induced by activation of sympathetic nerves is particularly important in dogs, where galanin is released into the venous effluent of the pancreas during pancreatic sympathetic stimulation in a quantity which is sufficient to inhibit insulin secretion [82].…”
Section: Sympathetic Nervesmentioning
confidence: 99%
“…These neuropeptides are both localised to the islet sympathetic nerve terminals. This is evident from several different species in which they are co-localised to the adrenergic marker, tyrosine hydroxylase or greatly depleted by 6-hydroxy-dopamine which selectively destroys the sympathetic nerve terminals [56, 77,78]. Galanin and NPY are also localised to nerve cell bodies in the celiac ganglion, as shown in dogs [56].…”
Section: Sympathetic Nervesmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemical studies have demonstrated galanin in the neural elements of the pancreas of several mammalian species such as pig [14,16], dog [5,14,23], cat [6], rat and mouse [13], baboon [23] and human [1,14,19]. Recently, we have reported striking findings on the presence of galanin-like immunoreactivity not only in the neural elements but also in the endocrine cells of the large islets of cattle, a large ruminant species [2,17].…”
mentioning
confidence: 95%
“…One of the extensively studied biological effect of galanin is its ability to regulate insulin secretion in pig [16], dog [5,9,15], rat [8,12,18], mouse [11] and human [1,3]. This physiological action of galanin coupled with its effect on pancreatic exocrine secretion [18,23] and release of other pancreatic hormones such as pancreatic polypeptide [3,20], glucagon [3,5,9,11,12,16] and somatostatin [3,5,9,16] [1,14,19]. Recently, we have reported striking findings on the presence of galanin-like immunoreactivity not only in the neural elements but also in the endocrine cells of the large islets of cattle, a large ruminant species [2,17].…”
mentioning
confidence: 99%